2016
DOI: 10.1007/s10854-016-4308-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlling A-center concentration in silicon through isovalent doping: mass action analysis

Abstract: It has been determined experimentally that doping silicon with large isovalent dopants such as tin can limit the concentration of vacancy-oxygen defects, this in turn, can be deleterious for the materials properties and its application. These results have been supported by recent calculations based on density functional theory employing hybrid functional. In the present study, we employ mass action analysis to calculate the impact of germanium, tin and lead doping on the relative concentrations of vacancyoxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
(62 reference statements)
1
2
1
Order By: Relevance
“…This is consistent to a recent model that considered the effect of isovalent doping (Ge, Sn, Pb) in Si [44]. Although carbon was not considered in that study it was demonstrated that only defects that had a strong interaction with vacancies (i.e.…”
Section: Impact Of Carbon Concentrationsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent to a recent model that considered the effect of isovalent doping (Ge, Sn, Pb) in Si [44]. Although carbon was not considered in that study it was demonstrated that only defects that had a strong interaction with vacancies (i.e.…”
Section: Impact Of Carbon Concentrationsupporting
confidence: 90%
“…C i and C i C s are the dominant carbon related defects, whereas C i O i Si I and C i O i defects become increasingly important for high temperatures and the higher initial carbon concentrations. It was previously calculated that the oversized (Pb and Sn) isovalent dopants impact the oxygen-vacancy defects [44], whereas here we showed that carbon does not. This is due to the limited formation of C i O i defects and the insignificant interaction of carbon atoms with vacancies.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…One of the first studies in this direction was reported by Brelot in 1972, [1] but there is still interest in this topic. [2][3][4][5][6] The main reason is that the isovalent tin impurity in silicon is one of the most efficient radiation-induced vacancy (V) traps. Therefore, it is suggested that Si:Sn can have a radiation hardening potential.…”
Section: Introductionmentioning
confidence: 99%